2019
DOI: 10.1017/cjn.2019.333
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Alzheimer’s Disease Patients: A 10-Year Follow-up Pilot Study in Shanghai

Abstract: ABSTRACT:Background:Identifying risk factors and mortality of individuals with Alzheimer’s disease (AD) could have important implications for the clinical management of AD.Objective:This pilot study aimed to examine the overall mortality of AD patients over a 10-year surveillance period in Shanghai, China. This study is an extension of our previous investigation on mortality of neurodegenerative diseases.Methods:One hundred and thirty-two AD patients recruited from the memory clinics of two hospitals in Shangh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Interestingly, a pilot study in Shanghai using hospital-based samples reported a similar survival trend of patients with AD compared with that of the general population. Poor cognitive status and comorbid diabetes had a negative impact on the survival of patients with AD,4 and a noteworthy association between AD and specific types of cancer was observed in China 16…”
Section: Data Source and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a pilot study in Shanghai using hospital-based samples reported a similar survival trend of patients with AD compared with that of the general population. Poor cognitive status and comorbid diabetes had a negative impact on the survival of patients with AD,4 and a noteworthy association between AD and specific types of cancer was observed in China 16…”
Section: Data Source and Analysismentioning
confidence: 99%
“…Compared with the 2010 census figures, China’s ageing population grew faster, and the incidence rate, morbidity and mortality of diseases associated with ageing were significantly higher 2. Alzheimer’s disease (AD) incidence continues to increase, and its social and economic burden is magnifying, posing major medical and social problems that threaten China’s urban and rural residents 3 4. According to a recent national cross-sectional study, China has 15.07 million individuals aged 60 years and over with dementia, including 9.83 million with AD, 3.92 million with vascular dementia and 1.32 million with other forms of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies, diabetes was associated with a high risk of death in patients with dementia. [ 55 , 56 ] Both AD and diabetes are chronic diseases that may share common pathologic features, [ 57 ] and there is increasing evidence of brain glucose dysregulation in AD. This may also be related to a faster annual rate of cognitive decline in AD patients, [ 58 ] and diabetes seems to promote specific neuropathologic processes that contribute to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…49 From one existing pilot study in China, patients with AD have a similar survival trend compared to the general population during 10-year follow-up. 50 and it remains an open question how to appropriately adjust findings for the uncertain differential competing risk from death in AD and non-AD individuals of the cohort. Second, considering the chief complaint of memory loss for most individuals during their first visit to clinicians, the elderly do not always seek medical service due to a lack of early definitive symptoms and due to stigmatization of the AD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the death from a chronic disease like AD is hard to determine, as most are recorded as hypostatic pneumonia, cachexia, or other complications using the ICD‐10 code 49 . From one existing pilot study in China, patients with AD have a similar survival trend compared to the general population during 10‐year follow‐up 50 . and it remains an open question how to appropriately adjust findings for the uncertain differential competing risk from death in AD and non‐AD individuals of the cohort.…”
Section: Discussionmentioning
confidence: 99%